2009
DOI: 10.1598/rt.62.6.5
|View full text |Cite
|
Sign up to set email alerts
|

“She's My Best Reader; She Just Can't Comprehend”: Studying the Relationship Between Fluency and Comprehension

Abstract: If reading fluency contributes to reading comprehension, then highly fluent readers should be expected to perform well in comprehension when reading materials are at their current grade level. The authors identified 171 elementary, middle, and secondary students who had been labeled by parents and teachers as strong readers and assessed as highly fluent readers. All students were given two narrative passages from the Critical Reading Inventory to assess their ability to react and respond to the text, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 24 publications
2
22
1
3
Order By: Relevance
“…Most ( n = 38) did not report the ethnic composition of participants. Of the 16 studies providing, at least, some information on students’ racial and ethnic backgrounds, 5 studies reported predominately (85% or greater) Caucasian samples (Applegate, Applegate, & Modla, 2009; Kucer, 2009; Rasinski, 1990; Shinn, Good, Knutson, Tilly, & Collins, 1992; Walczyk & Raska, 1992). Three studies had samples between 30 and 50% varied with respect to ethnicity (Carlisle, 1999; Fuchs et al, 1988; Pearman, 2008), and 3 studies referred more generally to students being of diverse backgrounds (Richgels, McGee, Lomax, & Sheard, 1987; Williams, 1991; Zinar, 1990).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most ( n = 38) did not report the ethnic composition of participants. Of the 16 studies providing, at least, some information on students’ racial and ethnic backgrounds, 5 studies reported predominately (85% or greater) Caucasian samples (Applegate, Applegate, & Modla, 2009; Kucer, 2009; Rasinski, 1990; Shinn, Good, Knutson, Tilly, & Collins, 1992; Walczyk & Raska, 1992). Three studies had samples between 30 and 50% varied with respect to ethnicity (Carlisle, 1999; Fuchs et al, 1988; Pearman, 2008), and 3 studies referred more generally to students being of diverse backgrounds (Richgels, McGee, Lomax, & Sheard, 1987; Williams, 1991; Zinar, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…Just 1 of the 54 studies in this review (Rasinski, 1990) did not explicitly describe how the retells were scored, and merely 4 studies reported exclusively using a qualitative approach—all of which relied upon an analysis of narrative story grammar elements (Applegate et al, 2009; Doty, Popplewell, & Byers, 2001; Hagtvet, 2003; Pearman, 2008). Among those latter 3 studies, only Pearman (2008) provided interrater reliability information (84%), which was below the mean but within the range of the interrater reliability data from quantitatively scored retells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, reading comprehension (RC) not only includes the ability to extract meaning from text but also involves the capacity to elaborate meaning by a thorough interaction with the text, integrating prior knowledge as well (Verhoeven & Perfetti, ). Indeed, being a good word decoder is clearly not sufficient to be a good text comprehender (Applegate, Applegate, & Modla, ). Success in RC involves the mastering of a large set of RC tasks: locating information found in the text, reporting main ideas, and making inferences based on both text and prior knowledge (Kintsch, ).…”
Section: From Reading To Reading Comprehensionmentioning
confidence: 99%